Meta-analysis of real-world evidence comparing non-vitamin K antagonist oral anticoagulants with vitamin K antagonists for the treatment of patients with non-valvular atrial fibrillation - Craig I. Coleman; Jean-Baptiste Briere; Laurent Fauchier; Pierre Levy; Kevin Bowrin; Mondher Toumi; Aurélie Millier; Vanessa Taieb; Olivia Wu (Taylor & Francis Group, 2019)
Introduction: Numerous real-world studies have compared non-vitamin K antagonist oral anticoagulants (NOACs) with vitamin K antagonists (VKAs) in patients with non-valvular atrial fibrillation (NVAF). A meta-analysis was performed to synthesize the available evidence. Methods: Systematic searches were performed through 12/2016 to identify non-randomized NVAF studies comparing NOACs with VKAs, and reporting effectiveness, safety, or persistence. Results: Of 562 citations identified, 49, 79, and 18 compared rivaroxaban, dabigatran, and apixaban, respectively, with VKAs and were included. Compared with VKAs, rivaroxaban was associated with a reduced risk of ischemic stroke (IS) (hazard ratio [HR] = 0.83, 95% confidence interval [CI] = 0.75-0.93), intracranial haemorrhage (ICH) (HR = 0.69, 95% CI = 0.52-0.90), and non-persistence (HR = 0.62, 95% CI = 0.60-0.65). Dabigatran was associated with a significantly lower risk of IS (HR = 0.80, 95% CI = 0.65-0.98) and ICH (HR = 0.45, 95% CI = 0.36-0.58), but not for non-persistence (HR = 0.91, 95% CI = 0.53-1.55), compared with VKAs. Apixaban was associated with a lower risk of ICH than VKAs (HR = 0.41, 95% CI = 0.28-0.60), but was not different to VKAs in terms of IS (HR = 1.01, 95% CI = 0.87-1.17) or non-persistence (HR = 1.08, 95% CI = 0.81-1.45). Conclusion: NOACs appear to be at least as effective and safe as VKAs for stroke prevention in patients with NVAF.